2016
DOI: 10.1016/j.bmc.2016.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Functional foldamers that target bacterial membranes: The effect of charge, amphiphilicity and conformation

Abstract: Snape, Timothy James, Dennison, Sarah Rachel and Patil sen, Yogita (2016) Functional foldamers that target bacterial membranes: the effect of charge, amphiphilicity and conformation. Bioorganic & Medicinal Chemistry, 24 (18) AbstractBy varying the molecular charge, shape and amphiphilicity of a series of conformationally distinct diarylureas it is possible to control the levels of phospholipid membrane lysis using membranes composed of bacterial lipid extracts. From the data obtained, it appears as though th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…The series of compounds In(N(SiMe 3 ) 2 ) 3 ( 1 ), In(N(SiMe 3 ) 2 ) 2 Cl⋅THF ( 2 ) and In(N(SiMe 3 ) 2 )Cl 2 ⋅(THF) n ( 3 ) were prepared by minor modifications of the literature method involving a salt metathesis reaction of Na(N(SiMe 3 ) 2 ) and InCl 3 . In the case of compounds 2 and 3 crystallographic studies confirmed the formulations (Figure ).…”
Section: Methodsmentioning
confidence: 69%
“…The series of compounds In(N(SiMe 3 ) 2 ) 3 ( 1 ), In(N(SiMe 3 ) 2 ) 2 Cl⋅THF ( 2 ) and In(N(SiMe 3 ) 2 )Cl 2 ⋅(THF) n ( 3 ) were prepared by minor modifications of the literature method involving a salt metathesis reaction of Na(N(SiMe 3 ) 2 ) and InCl 3 . In the case of compounds 2 and 3 crystallographic studies confirmed the formulations (Figure ).…”
Section: Methodsmentioning
confidence: 69%
“…The higher obtained activities of these compounds can be attributed to the presence of macrocyclic octapeptide ring, the Schiff base of 3-pyridine carbaldehyde and the hydrazide bond in compounds 9, 4b and 2, respectively. Generally, the antimicrobial activity of the synthesized peptides can be due to the interaction of the peptides with microbial cell membranes, and thus affecting the integrity of the cell walls [33,34]. Furthermore, peptides have been reported to effect microbial cells intracellularly by interacting with cellular DNA or enzyme machinery [35].…”
Section: Antimicrobial Testingmentioning
confidence: 99%
“…(4) (5)We have an on-going interest in the established phenomenon that diarylamides and diarylureas adopt discrete three-dimensional conformations that place the aromatic rings in either a stacked or unstacked arrangement dependent on their N-substitution pattern, (6)(7)(8)(9)(10) and within the context of cancer therapy, we have previously exploited this through the synthesis of a range of diarylurea-based combretastatin A4 analogues (e.g. 1, Figure 1).…”
Section: Introductionmentioning
confidence: 99%